First in human: the effects of biventricular pacing on cardiac output in severe pulmonary arterial hypertension - Oktay, Ahmet Afşin; Mandras, Stacy A.; Shah, Sangeeta; Kancharla, Krishna; Shams, Omar F.; Pascual, Mario I.; Morin, Daniel P. (Heart and vessels, 2020)
Pulmonary arterial hypertension (PAH) carries high morbidity and mortality despite available treatment options. In severe PAH, right ventricular (RV) diastolic pressure overload leads to interventricular septal bowing, hindering of left ventricular diastolic filling and reduced cardiac output (CO). Some animal studies suggest that pacing may mitigate this effect. We hypothesized that eliminating late diastole via ventricular pacing could improve CO in human subjects with severe PAH. Using minimal to no sedation, we performed transvenous acute biventricular (BiV) pacing and right heart catheterization in six patients with symptomatic PAH. Hemodynamic measurements were taken at baseline and during BiV pacing at various 20-ms intervals of V-V timing. We compared baseline CO to (1) CO while pacing the RV first by 80 ms (mimicking RV-only pacing), and then to (2) CO during pacing at the V-V timing that resulted in the highest CO. All participants were female, PASP 74 ± 14 mmHg, QRS duration 104 ± 20 ms. Compared with baseline, the CO decreased when the RV was paced first by 80 ms (7.2 ± 1.0 vs. 6.2 ± 1.1 L/min, p = 0.028). Pacing with optimal V-V timing produced CO similar to baseline (7.2 ± 1.0 vs. 7.4 ± 1.4, p = 0.92). Two patients (33%) met the predefined endpoint of a 15% increase in CO during pacing at the optimal V-V timing. In symptomatic PAH, V-V optimized acute BiV pacing does not consistently improve CO. However, acute BiV pacing did improve CO in a subset of this cohort. Further research is needed to identify predictors of response to cardiac resynchronization therapy in this population.